Análise da variação espacial e temporal da dinâmica trófica e razão isotópica de carbono e nitrogênio de Diapoma alburnus (Pisces, Characiformes) - Rosemberg, Cibele Boeira Batista (2016)
Studies focusing on the trophic dynamics of ecosystems have been using information concerning the analysis of stomach contents of species, from direct observation of feeding activity, as well as from the signature of stable isotopes, such as carbon and nitrogen. The evaluation of stomach contents reflects feeding for a limited period of time, while the stable isotopes analysis reflects information on a larger time schedule, which helps to understand the trophic structure of ecosystems and allows the construction of assumptions regarding the energy chain. The combined use of these two techniques may, therefore, lead to a better understanding of spatial and temporal variations of the trophic dynamics. Thus, the current study aims to quantify the sources of isotopic signature variations of δ13C and δ15N in the tetra Diapoma alburnus (Hensel, 1870) (Characiformes) by using spatial, seasonal and interannual variation sources, analyzing the isotopic signatures in association with the stomach contents of individuals of different sizes. Sampling occurred on the northern coastal plains of Rio Grande do Sul state, Brazil, on Barros, Fortaleza, Itapeva, Lessa and Pinguela Lagoons, from June 2014 to April 2015. For stomach content analysis, 240 fish were used per sampling site. The relative importance of each food item was estimated based on the Frequency of Occurrence. For stable isotopes analysis, we used specimens of different sizes (2 cm to 8 cm) collected in different seasons in each lagoon, totaling 242 animals. The results concerning stomach content analysis showed that the most common items were Insecta (45%) and Cladocera (42%). Regarding the temporal variation, the results differed significantly (Kruskal-Wallis) for Algae (p = 0.0175) and vegetable materials (p = 0.0260). Additionally, a spatial variation was detected for Insecta (p = 0.0036), Cladocera (p = 0.0008) and Araneae (p = 0.0282). The signatures of δ13C and δ15N revealed spatial and temporal variations, both between different seasons and successive years. The results indicated the presence of high temporal and spatial variability in the use of resources, which reflects a great trophic plasticity of Diapoma. alburnus in regard to cyclical or stochastic availability of food items. Therefore, the use of stable isotopes to analysis the trophic dynamics of a species is a suitable tool that presents only a snapshot of the food source, reflecting a wider time window in comparison to the analysis of stomach contents, but still limited to make generalizations concerning time or space.